Pengembangan e-Modul Materi Senyawa Hidrokarbon Berbasis Problem Based Learning Di Sma/Ma - Ersia Kartika Putri; Epinur Epinur; Afrida Afrida (Syntax Idea, 2026)
This study aims to examine the development process, feasibility, teacher assessment, and student response toward a Problem Based Learning (PBL)-based e-Module on Hydrocarbon Compounds. This is a development research study employing the Lee & Owens model with five stages. The subject of this study were student of class XI A at MAN 2 Bungo. Data collection instruments include interview sheets, student needs analysis questionnaires. validation sheets from subject matter experts and media experts, teacher assessment questionnaires, and student response questionnaires. Data were analyzed using qualitative and quantitative descriptive methods. The findings reveal that the e-Module was developed through a series of stages, beginning with the analysis of student needs and characteristics, the design of flowcharts and storyboards, the development process using Canva Design and Heyzine Flipbook applications, and finally the implementation through small group trials. The average score from the subject matter expert validation was 4.4 (Excellent), media expert validation was 4.5 (Excellent), teacher assessment was 4.8 (Excellent), and student responses reached 90% (Excellent). The researcher recommends applying PBL-based e-Modules to other subject areas using a variety of applications, with simpler and more adaptive designs that accommodate different student learning styles. Additionally, large-scale trials and effectiveness tests are recommended for future research to measure the actual impact of e-Modules on the learning process.